Differential effect of metabolic alkalosis and hypoxia on high-intensity cycling performance - Flinn, S.; Herbert, K.; Graham, K.; Siegler, J. C. (The Journal of Strength and Conditioning Research, 2014)
The purpose of this study was to investigate the effects of sodium bicarbonate (NaHCO3) ingestion and acute hypoxic exposure on repeated bouts of high-intensity cycling to task failure. Twelve subjects completed 4 separate intermittent cycling bouts cycling bouts to task failure (120% peak power output for 30-second interspersed with 30-second active recovery) under the following conditions: normoxia (FIO2% at 20.93%) alkalosis (NA), normoxia placebo (NP), hypoxia (FIO2% at 14.7%) alkalosis (HA), and hypoxia placebo (HP). For the NA and HA trials, the buffer solution (0.3 g/kg of NaHCO3) was dispensed into gelatin capsules and consumed over 90 minutes with 1 L of water. Whole-blood acid-base findings demonstrated metabolic alkalosis in both NA and HA before exercise (HCO3-: 32.8 ± 1.8 mmol/L). Time to task failure was significantly impaired in the hypoxic conditions (NA: 199.1 ± 62.3 seconds, NP: 183.8 ± 45.0 seconds, HA: 127.8 ± 27.9 seconds, HP: 133.3 ± 28.7 seconds; p < 0.001; n2 = 0.7). There was no difference between the HA and HP conditions (p = 0.41); however the 2 normoxic conditions approached significance with the NA condition on average resulting in approximately 15-second improvement in time to task failure (p = 0.09). These findings suggest that an acute decline in FIO2% consistent with hypoxic exposure is more inhibiting than metabolic acidosis during intermittent high-intensity cycling to task failure. In application, the use of hypoxia and NaHCO3 concurrently to improve performance under these conditions does not seem warranted.